If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -2x = -19 Solving -7 + -2x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2x = -19 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = -19 + 7 -2x = -19 + 7 Combine like terms: -19 + 7 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) | | 17=2x+3 | | 4(2x+1)=x+4 | | 18-10(x-1)=4x | | 2-4/2 | | 1/3(5y-1) | | 8+f(4/5)=0 | | -8x-(3x+6)=4-1x | | 5x-4=1-x | | (y^2-4y+3)/(5y^2-40y+35) | | 4y-3(2y-7)=5y+12 | | v^2-v=30 | | x-5+3x/4=-5+7x/4 | | x+2-8=14 | | 28+a+(-48.08)*(1.414213562)=0 | | 2t+3=-12 | | 34+a+(-48.08)*(1.414213562)=0 | | 5(-3b+2)=40 | | 34+a+(-48.08)*1.414213562=0 | | 10+9(x-2)=13x-4(x+4) | | 10k+13r=(276)(12) | | 10a+120=8 | | -(2x-8)+1=7x+9(1-x) |